Domestic Violence against Married Women in an Urban Informal Settlement - Acharya, Bala Ram (KMC Journal, 2026)
Domestic violence is common in every society at different levels, but it is often hidden in urban contexts. Urban informal squatter known as unmanaged settlements are home to economically disadvantage and socially underprivileged families. The daily life of women in informal settlements is influenced by patriarchal rigidity and multiple associated vulnerabilities that constrain women. The lived experiences of women under the social and cultural constraints of patriarchy in Kathmandu’s Balkhu Corridor between the ages of 20 and 60 are examined in this study. This study is based on a qualitative approach. Data was collected from ten squatters, known as unmanaged settlement, women through an extensive case study discussion. Qualitative data were analyzed by organizing and collecting the codes of participants’ words. Meaning of data was established from themes and patterns in qualitative information. Findings show psychological violence is reported more than repeatedly physical injury among the participants. Women also face emotional pain, mistrust, fear, control and financial dependence frequently within the family. Many effects remain silent because of social pressure, cultural expectations of respect, and fear of losing family dignity. Alcohol use, economic strain, and insecure jobs make their situation worse for violence at large. Despite the deep pain, women show internal strength by staying patient, providing family support, and looking after their children. The study shows that domestic violence is a social construct, not just an individual interferes. It shows the need to listen more closely to women’s life histories. It also reminds us to observe their lives closely. Social perceptions shape their domination and economic pressure intensifies their suffering. Family expectations under patriarchy further deepen their suffering in the urban setting.